Leaf gas exchange and mineral nutrition of Clitoria Ternatea intercropped with forage cactus under supplemental brackish water irrigation (Acta Scientiarum. Agronomy, 2025)
Supplemental irrigation using moderately saline water and intercropping are effective strategies for mitigating the adverse effects of water stress on leaf physiology, particularly during dry periods. This study aimed to assess the impact of supplemental irrigation with brackish water (3.0 dS m-1) on leaf gas exchange and mineral concentrations in butterfly pea (Clitoria ternatea L.) when intercropped with forage cactus (Opuntia stricta). Conducted under a semi-arid climate in 2022 and 2023, the experimental design was a randomized block in split plots, with four replicates. The main plots consisted of two water scenarios: no irrigation and supplemental irrigation. The subplots comprised three cropping systems: butterfly pea in monoculture (B) (1.0 x 0.1 m), forage cactus (2.0 x 0.1 m) intercropped with a line of butterfly pea (P+1B), and forage cactus (3.0 x 0.1 m) intercropped with two lines of butterfly pea (P+2B). Supplemental irrigation was applied to the butterfly pea from February to June during dry spells and fully during the onset of the dry season (July and August). This irrigation approach alleviated water stress impacts on stomatal conductance, net photosynthesis rate, transpiration rate, and internal CO2 concentration, and enhanced the levels of K+, Ca2+, Cl-, and Na+. Additionally, the P+2B system, when supplemented, led to increased accumulation of N and P. Intercropping improved leaf gas exchange and reduced Cl- concentration in C. ternatea, thus benefiting its agronomic performance.